2018
DOI: 10.4102/sajp.v74i1.452
|View full text |Cite
|
Sign up to set email alerts
|

Anterior knee pain and its intrinsic risk factors among runners in under-resourced communities in Ekurhuleni, Gauteng

Abstract: BackgroundAnterior knee pain (AKP) is the most common injury among runners, especially in females and young runners. Because of a deficit of rehabilitation services in under-resourced communities, runners train and compete with injuries, resulting in further complications.ObjectivesThis study aimed to determine the prevalence and modifiable intrinsic risk factors for AKP among runners in under-resourced communities in Ekurhuleni, Gauteng Province.MethodThis cross-sectional study included a population of 347 ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 38 publications
0
36
0
Order By: Relevance
“…Anterior knee pain was found to be strongly associated with age ( 2 = 6.48, p = 0.04) followed by the group of young people [7] Kunene et al [7] (n = 33, 18%) and, lastly, running experience ( 2 = 8.39, p = 0.04). Participants with 1-3-years of running experience was the most affected group (n = 22, 12%) ( Table 2).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Anterior knee pain was found to be strongly associated with age ( 2 = 6.48, p = 0.04) followed by the group of young people [7] Kunene et al [7] (n = 33, 18%) and, lastly, running experience ( 2 = 8.39, p = 0.04). Participants with 1-3-years of running experience was the most affected group (n = 22, 12%) ( Table 2).…”
Section: Resultsmentioning
confidence: 93%
“…[6] In particular, tight hamstrings and weakness of the iliotibial band and quadriceps, weak hip control muscles and patellar tilt abnormalities were found to be significant when associated with AKP in an under-resourced community in South Africa. [7] It is therefore critical that the intrinsic risk factors be considered in the management of AKP in order to improve management outcomes. [7] Establishing extrinsic risk factors is another important component to be considered when dealing with the management of AKP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other factors may include tight iliopsoas muscles, tightness of the gastrocnemius complex, foot pronation, general joint laxity, leg length discrepancy, patellar glide abnormalities, and patellar hypermobility. [4,5] Kunene et al [5] also found that a heavy training load, lack of warm-up exercises during training, poor condition of running shoes, and downhill running significantly contribute to AKP among runners. [6] The incidence of sports injuries and their associated problems continues to increase among athletes, more especially among those in the poorer communities who live under unfavourable socioeconomic conditions.…”
mentioning
confidence: 99%
“…[3] Various factors were found to contribute to this condition. According to Kunene et al [4] tight hamstring and iliotibial band muscles, weak quadriceps muscles, weak gluteal muscles (resulting in poor hip control) and patellar tilt problems, were found to contribute significantly to AKP. Other factors may include tight iliopsoas muscles, tightness of the gastrocnemius complex, foot pronation, general joint laxity, leg length discrepancy, patellar glide abnormalities, and patellar hypermobility.…”
mentioning
confidence: 99%